Normative Juridical Analysis And Legal Sanctions For Land Ownership Rights For Catholic Church Bodies In Indonesia - Suhartoyo Suhartoyo (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Normative Legal Analysis and Legal Sanctions of Land Ownership Rights for Catholic Church Bodies in Indonesia: Case Study of the Decision of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21/Pnj/Kem-ATR/BPN/BPN/2024. This study analyzes the normative legal and legal sanctions on land ownership rights for Roman Catholic church bodies in Indonesia based on Decision Number 21/PNJ/Kem-ATR/BPN/VI/2024. This study aims to understand the rights and obligations of Roman Catholic Church bodies in owning and using land, as well as the legal implications of the decision. The results of the study show that Decision Number 21/PNJ/Kem-ATR/BPN/VI/2024 provides legal certainty for Catholic Church bodies in Indonesia to have land ownership rights. However, land ownership rights can only be granted as long as the land is used for purposes directly related to religious endeavors and in carrying out its activities is not solely for profit. This study also found that there are legal sanctions that can be applied if Catholic Church bodies in Indonesia violate or misuse land ownership rights, such as revocation of ownership rights, fines or administrative sanctions, and return of land. The implications of Decision Number 21/PNJ/Kem-ATR/BPN/VI/2024 regarding land ownership rights for Catholic Church bodies in Indonesia are to increase legal certainty, develop religious activities, improve the quality of services, and strengthen the existence of Catholic Church bodies in Indonesia as religious institutions that play a role in society.